The Determinants of The Brain Drain Phenomenon in Educational Migration Activities - Made Dwi Setyadhi Mustika; Ni Nyoman Yuliarmi (Universitas Udayana, 2024)
During this time, the main reason someone migrates is related to themotivation to get a better job. However, the other reason that can not be ignored isthe expectation to get the opportunity of having a higher level of education. Aphenomenon that occurs following the educational migration is many educationalmigrants did not return to their origins after finishing their studies, and would chooseto work in the destinations. This phenomenon is known as brain drain, which refers tothe condition where the educational migrants did not return to their origins afterfisnishing their studies in the destinations. This study covers educational migrationactivities between regions in Indonesia, so the term used to describe this condition isthe domestic brain drain.This study aimed to analyze the determinant of the brain drain phenomenon ineducational migration activities. By using panel data of the Indonesian Family LifeSurvey (IFLS) wave 5, which were processed using the Logistic Regression Modelmethod, the result suggested that about 49.08 percent of educational migrants inIndonesia chose not to return to their origins after finishing their studies. Theydecided to work in the destination or in other areas outside the area of their origins.Their decisions were significantly affected by the amount of salary/income, maritalstatus, location of parents' residence, health facilities, sex, age, age square, provinceof the origin, and geographical. Partially, marital status, the residence of the parents,age square, and geographical, have a negative impact to migrant’s decision.Meanwhile, health facilities, sex, and age have a positive impact to migrant’sdecision.